Unexpected reaction patterns enable simultaneous differentiation of H2S, H2Sn and biothiols. Issue 56 (25th June 2019) - Chen, Wenqiang; Fu, Li; Chen, Chunfei; Xiao, Junan; Li, Wenxiu; Zhang, Liangliang; Xiao, Qi; Huang, Chusheng; Sheng, Jiarong; Song, Xiangzhi
Abstract : A robust fluorescent probe, MCP1, was developed for triple-detection of H2 S, H2 S n and biothiols for the first time. Abstract : A robust fluorescent probe, MCP1, was developed for triple-detection of H2 S, H2 S n and biothiols for the first time. Introduction of H2 S, H2 S n and biothiols toMCP1 lead to distinct emission peaks at 508, 576 and 469 nm, respectively, enabling simultaneous detection of H2 S, H2 S n and biothiols from distinct emission channels.